International Financial Reporting Standards and Real Earnings Management - Keong, Ooi Chee; Mohamad, Shafi; Ehsanullah, Syed (Asian Journal of Empirical Research, 2019)
We have attempted to investigate the impact of adopting the International Financial Reporting Standards (IFRS) on real earnings management (REM) in this study, along with a thorough examination to determine the relationship between IFRS and REM. The study is primarily based on 178 listed firms from different industrial sectors in Malaysia, wherein IFRS had finally been implemented in 2008. For more adequate estimations and requisite results, we have included data of eight years i.e., 4 years before the implementation of IFRS and 4 years after its implementation, in our sample. Our results showed positive association between IFRS and REM, accordingly, precisely suggesting that after the implementation of IFRS, these firms were found to be engaged more in less detectable REM, and also exhibiting quite a poor financial reporting quality apparently below international standards.